1993
DOI: 10.1084/jem.178.5.1507
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of B lymphopoiesis during normal pregnancy.

Abstract: SummaryWe describe a dramatic reduction in numbers and activity of committed B lymphocyte precursors in the bone marrow of normal pregnant mice. Changes in cells responsive to were evident as early as 6.5 d of pregnancy and values were <10% of normal at parturition. B lineage precursors, identified by display of CD45R and absence of surface IgM, were also substantially depressed, and subpopulations representing different stages in the B lineage were assessed by three-color flow cytometry. Early pro-B ceUs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(145 citation statements)
references
References 60 publications
8
132
0
5
Order By: Relevance
“…Previously, we have shown that pre-activated MZ B cells numbers were increased in the spleen during pregnancy and proposed that this may represent an evolutionary acquired mechanism tending to overcome the strong reduction of B cell lymphopoiesis occurring during this critical period of time, thus ensuring a proper defense (Medina et al, 1993;Muzzio et al, 2014). Indeed, using a mouse model of pregnancy failures (Bobé et al, 1986) we could later confirm the crucial role of MZ B cells in pregnancy wellbeing by showing that pregnant mice developing normal pregnancies but not those suffering from pregnancy failures display an expansion of the MZ B cell compartment (Muzzio et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that pre-activated MZ B cells numbers were increased in the spleen during pregnancy and proposed that this may represent an evolutionary acquired mechanism tending to overcome the strong reduction of B cell lymphopoiesis occurring during this critical period of time, thus ensuring a proper defense (Medina et al, 1993;Muzzio et al, 2014). Indeed, using a mouse model of pregnancy failures (Bobé et al, 1986) we could later confirm the crucial role of MZ B cells in pregnancy wellbeing by showing that pregnant mice developing normal pregnancies but not those suffering from pregnancy failures display an expansion of the MZ B cell compartment (Muzzio et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Bone marrow or spleen cells were prepared and suspended in 1 ml of assay medium as described (32). The semisolid agar colony-forming units (CFU) assay for lymphoid clones responsive to IL-7 used 1 ng/ml recombinant mouse IL-7.…”
Section: Colony-forming Cell Assaymentioning
confidence: 99%
“…It would therefore make sense that this energetically costly process is suppressed in pregnant leptin-treated females in response to increased reproductive investment. Most studies across mammalian species demonstrate decreased immunity, including production of certain antibodies, during pregnancy (Weinberg 1984;Medina et al 1993). In fact, previous studies in Siberian hamsters show decreased anti-KLH IgM response during pregnancy (Drazen et al 2003).…”
Section: Discussionmentioning
confidence: 99%